Mood Disorder due to Herpes Simplex Encephalitis with Neuroimaging Findings Limited to the Right Hemisphere and Cerebellum: Case Report - TOPÇUOĞLU, VOLKAN (ORTADOGU AD PRES & PUBL CO, 2012)
Herpes simplex (HSV) encephalitis may cause psychiatric syndromes including mood disorder episodes. A case of secondary mood disorder after HSV encephalitis is reported in this paper. The aim of this case presentation is to discuss the neuroanatomic regions of the brain associated with secondary mood disorders in the light of the patient's neuroimaging findings. A 62-year-old patient with HSV encephalitis developed a depressive episode for the first time followed by a manic episode. The patient's magnetic resonance imaging scan showed cerebral atrophy mainly affecting the right temporal lobe and cerebellar atrophy as well as perfusion defects in the right amygdala, right basal ganglion and right temporal cortex as seen in the single-photon emission computed tomography (SPECT). The findings were consistent with defects located exclusively in the right cerebral hemisphere. To the best of our knowledge, the cerebellar pathology has been demonstrated for the first time in a mood disorder case secondary to HSV. Neuroimaging findings of the secondary mood disorder cases may contribute to a better understanding of the neuroanatomical regions of this, yet not fully understood mood disorder.
Keywords: Encephalitis; herpes simplex; bipolar disorder; aged; BIPOLAR DISORDER; FUNCTIONAL NEUROANATOMY; MANIA SECONDARY; OLD-AGE; STROKE